Efficacy of Hyaluronic Acid Injection for Temporomandibular Joint Disorders with and without Arthrocentesis - Twana Hoshyar Saleem (Erbil Dental Journal)
Temporomandibular disorder affects millions of people worldwide. Temporomandibular joint internal derangement, is a common condition. Temporomandibular joint internal derangement is a progressive disorder that begins with clicking during nor- mal opening and progresses to restricted mouth opening (closed lock). Arthrocentesis and Visco supplementation as Hyluronic acid are minimally invasive techniques that involves wash out the joint and replacement of synovial fluid by intra-articular injection of Hyaluronic Acid which restores its concentration and molecular weight in joint cavity.